Green Roof Technology as a Sustainable Strategy to Improve Water Urban Availability. Issue 9 (February 2019) - Semeraro, Teodoro; Aretano, Roberta; Pomes, Alessandro
Abstract: The scale of the potential impacts of climate change is uncertain but, concurrently with other demographic, land-use, socioeconomic changes, it is affecting water availability and demand and increasing competition for water. As temperature increases, evaporation increases, resulting in droughts and devastating effects on fresh water supplies. Water will be one of the key resources for a sustainable urban development. Making clean water available in the next forty or so years will require the extending of the service to 3.7 billion more residents in urban areas. Therefore, it is necessary to promote an engineered redistribution of fresh water in space and time. This problem must be solved in a sustainable way using an innovative Green Infrastructure (GI) able to increase the water provision in urban systems realizing the recovery of rainwater and domestic water and reusing the same for irrigation and non-potable uses. Therefore, the aim of this research is to develop a project idea of GI focused on the reuse of water resource in a condominium of 40 housing units located in Lecce, south Italy. In particular, the project will exploit the free areas on the roof of the building, accounting a total surface of about 900 sqm. The project involves the construction of a green roof to develop the ecological functions linked to the purification of wastewater like in a Constructed Treatment Wetland (CTW) that represents a low-cost alternative to conventional secondary or tertiary wastewater treatment. This green roof allows the reuse of wastewater on site for sanitary, garden activities and other uses in the building, reducing the exploitation of the already scarce regional freshwater resources. The project idea also includes the possibility of using aromatic and medicinal plant species for phytoremediation, with potential applications in phytotherapy and cosmetics. CTWs produce ecosystem services like ones provided by wetlands and, therefore, act as sinks of CO2 . Moreover, it is widely recognized that the green roof reduces the heating of the buildings caused by the solar irradiation, thus reducing the consumption of energy necessary to cool the apartments. So, the green roof turns from an unused cemented roof into a source of ecosystem services related to both the reuse of water resources and the development of potential economic activities. The cost of the work can be reduced by government incentives for the development of gardens in condominiums or for energy efficiency of the building. At the municipal level, the replication of this project on many buildings could reduce the water demand for residential areas as well as can mitigate the island heat effect that afflicts urban area during the summer and improve the quality of life in the city. This approach offers many opportunities for integration of water resource conservation, economic development and public health promotion.